BACTERIA ASSOCIATED WITH URINARY TRACT INFECTIONS AND THEIR SUSCEPTIBILITY TO HERBAL EXTRACTS - MIR NAIMAN ALI,; MOHAMMED MAZHARUDDIN KHAN, (International Journal of Pharma and Bio Sciences, 2016)
In the present study 500 urine samples were collected from different diagnostic laboratories of Hyderabad, India. 350 urine samples were scored as positive UTI and a total of 211 bacterial cultures were isolated belonging to 5 species: Escherichia coli (43%); Klebsiella pneumoniae (23%); Pseudomonas aeruginosa (19%); Enterobacter faecalis (10%) and Proteus mirabilis (4%). Three selected plant extracts (Allium sativum, Mentha piperita, and Zingiber officinale) were used to test their antibacterial activity activity by agar well diffusion assay and Minimum inhibitory concentration. Aqueous, ethanolic and methanolic extracts were used; highest antibacterial activity was recorded with ethanolic extracts of Zingiber officinale on E. coli and least against K. pneumoniae with diameter of inhibition zones (DIZ) of 20.0 ± 0.60 and 9.0 ± 1.0 mm respectively. Phytochemical analysis revealed the presence of active compounds such as phenolics, tannins, alkaloids and flavonoids. The results clearly demonstrated strong antibacterial activity of extracts on all UTI isolates than with standard antibiotics.